KEHIDUPAN SOSIAL EKONOMI PENGRAJIN ROTAN DI DESA SAIBI SAMUKOP KECAMATAN SIBERUT TENGAH (1970-2000) - Sukarsih, Irah; Kaksim, Kaksim; Aziz, Zulkifli (Pendidikan Sejarah, 2013)
ABSTRACTÂ This thesis examines the Socio-Economic Life in the Village Craftsmen Rattan Saibi Samukop Central District of Siberut. The research problems can be formulated as follows : (1) who was the first to introduce a cane in the village of Siberut Saibi Samukop Central District, (2) how the development of social and economic life of rattan craftsmen in the village of Siberut Saibi Samukop Central District, (3) how the management and sale of rattan handicrafts in the village Saibi. This study aims to (1) To clarify who was first to introduce cane in the village of Siberut Saibi Samukop Central District, (2) To explain the development of social and economic life of rattan craftsmen in the village of Siberut Saibi Samukop Central District, (3) To explain how the management and sale of rattan in the Village District Saibi Samukop Middle Siberut.This study uses historical method with the following steps : (1) heuristic of finding and collecting information of primary and secondary sources, (2) criticism of sources including internal and external criticism is by testing for the authenticity of the source or the material is determined, (3) interpret the activities of interpretation using the data that has been collected, (4) the stage of writing the history of historiography or a presentation of research results in the form of thesis.The results of the study in 1970 Samukop Saibi villagers were relocated from Southwest Siberut Simatalu the number 26 KK sageilepak tribes, whereas the number of tribes saudeinu 10 families. Socio- economic life of the people in the Village District Saibi Samukop Middle Siberut can see several indicators, namely: (1) population, (2) livelihood, (3) management and sales, (4) income, (5) housing, (6) education. Development of social and economic life of rattan craftsmen in the village of Siberut Saibi Samukop Central District due to a variety of craft tanggan developed societies to make household appliances made of rattan.From the above results it can be concluded that there has been a change in the socio-economic life of the people in the village of rattan craftsmen Saibi Samukop Middle District of Siberut, because of the rattan in 1970 to 2000. So peoples lives in the village of rattan craftsmen Saibi Samukop Middle District of Siberut has improved and increased.Â Key words: Socio-Economic Life, Rattan Craftsmen, Village Saibi Samukop